EPICARDIAL OBESITY AND A RANGE OF METABOLIC RISK FACTORS RELATION WITH THE PREVALENCE INDEX OF CORONARY ATHEROSCLEROSIS - G. A. Chumakova; N. G. Veselovskaya; A. V. Ott; O. V. Gritsenko (Кардиоваскулярная терапия и профилактика)
Aim. To assess the relation of epicardial fat tissue thickness (EFTT) and other metabolic risk factors with the index of coronary atherosclerosis Spread (CASI) in obese patients. Material and methods. Totally 186 men included (54,4±9,1 y.o.) with coronary heart disease (CHD) and obesity. By the results of coronary arteriography we calculated Gensini Score of CASI. All patients underwent laboratory tests with the measurement of basic and additional metabolic risk factors and echocardiography with EFFT measurement. Results. By the data of regression analysis we selected 7 predictors significantly related to EFTT: CASI (β=0,390), resistine (β=0,453), glucose (β=152), adiponectine (β=-0,175), high density lipoproteides cholesterol (β=-0,138), interleukine-6 (β=0,118), and tumor necrosis factor-α (β=0,117). Measurement of the predictors values led in 52,1% to the changes of CASI value (R²=0,521). Conclusion. In obese patients the assessment of the parameters described makes possible to circle a high risk group for unsymptomatic CHD forms with the aim for on-time investigation of patients and for early preventive interventions.